Altered Serum IL-35 Levels and IL-37 Gene Expression in Patients with Parkinson's Disease: Focus on Emerging Cytokines - Akbari Gavabari, Fariba; Rastegari-Pouyani, Mohsen; Afshar, Saied; Mazdeh, Mehrdokht; Talebi-Ghane, Elaheh; Eftekharian, Mohammad Mahdi (Iranian journal of immunology, 2025)
Parkinson's disease (PD) is increasingly recognized as a condition driven by both central and peripheral inflammatory responses, largely mediated by cytokine activity. To assess IL-35 (P35 and Ebi3 subunits) and IL-37 gene expression, along with the serum levels of IL-35 protein in patients with PD compared to healthy controls. Cytokine gene expression was measured using the qRT-PCR technique, while IL-35 serum levels were measured using the ELISA method. The data obtained were analyzed using a Bayesian regression model in the R software. The results revealed that the expression of P35 gene, of the two subunits of IL-35, did not differ significantly between the two groups. However, Ebi3 and IL-37 transcript levels were significantly lower in patients compared to healthy individuals (p<0.001). In contrast, IL-35 serum level in patients showed a significant increase compared to the control group (p=0.016). Notably, IL-37 expression showed a negative correlation with age (p=0.004). . We also observed positive and significant correlations between the gene expression of P35 and Ebi3 (p= 0.02, r= 0.4), P35 and IL-37 (p= 0.008, r= 0.45), and Ebi3 and IL-37 (p= 0.016, r= 0.41). In conclusion, our study revealed a higher serum protein level of IL-35 in PD patients compared to the healthy control group. Meanwhile, gene expression levels of IL-37 and Ebi-3 were significantly reduced. These alterations in the expression of these cytokines are suggested to be partly responsible for the immune system dysregulation in this disease.